2017
DOI: 10.1021/acsami.7b08433
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Reduced Graphene Oxide via Thiol–Maleimide “Click” Chemistry: Facile Fabrication of Targeted Drug Delivery Vehicles

Abstract: Materials based on reduced graphene oxide (rGO) have shown to be amenable to noncovalent functionalization through hydrophobic interactions. The scaffold, however, does not provide sufficient covalent linkage given the low number of reactive carboxyl and alcohol groups typically available on the rGO. The integration of clickable groups, particularly the ones that can undergo efficient conjugation without any metal catalyst, would allow facile functionalization of these materials. This study reports on the nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 34 publications
(84 reference statements)
0
38
0
Order By: Relevance
“…Moreover, some charged polysaccharides such as chitosan, hyaluronic acid, and chondroitin sulfate could have interactions with oppositely charged drug molecules, which could also help to control drug loading and releasing [5,18]. Additionally, graphene family materials have a conjugated structure, which can absorb drug molecule through π-π interactions [18,[23][24][25][26][27][28]. Moreover, the oxygen permeability of CS film had been confirmed by previous research [29].…”
Section: Introductionmentioning
confidence: 61%
“…Moreover, some charged polysaccharides such as chitosan, hyaluronic acid, and chondroitin sulfate could have interactions with oppositely charged drug molecules, which could also help to control drug loading and releasing [5,18]. Additionally, graphene family materials have a conjugated structure, which can absorb drug molecule through π-π interactions [18,[23][24][25][26][27][28]. Moreover, the oxygen permeability of CS film had been confirmed by previous research [29].…”
Section: Introductionmentioning
confidence: 61%
“…Using thiol-maleimide chemistry, they modify rGO with cyclic peptide c(RGDfC) as a targeting ligand for targeted delivery of DOX to cancer cells. The in vitro studies performed with MDA-MB-231 cell line indicated that DOX loaded rGO/dopa-MAL-c(RGDFC) was more effective than free DOX in killing the cancer cells after exposure to 980 nm laser irradiation (2 W/cm 2 ) for 10 min [117]. This was attributed to the enhancement of chemotherapy with PTT from the endocytosed nanocomposite upon NIR laser exposure for targeted synergistic cancer cell killing.…”
Section: Chemotherapy/phototherapymentioning
confidence: 99%
“…Oz et al reported the noncovalent association of a maleimide-catechol compound (DOPA-MAL) with rGO from π – π interactions and hydrogen bonds. This nanosystem has been associated with doxorubicin (DOX) to evaluate the treatment of cervical cancer (HeLa) and breast cancer (MDA-MB-231) [ 169 ].…”
Section: Reviewmentioning
confidence: 99%